Prevalência de HIV, HBV, HCV e sífilis em pessoas privadas de liberdade, região metropolitana de Belo Horizonte, Minas gerais, 2018-2019. - Homero Campos Reis (2020)
The prevalence of sexually transmitted infections (STI) in the population deprived of freedom is higher than in the general population. In Brazil, there are some studies on STIs detainees, but data are still limited. This study describes the prevalence of HIV, Hepatitis B, Hepatitis C, and Syphilis in a population deprived of freedom in a temporary correctional facility in the metropolitan region of Belo Horizonte and its risk factors. In light of these considerations, the question that guided this study was: how important it is to know the prevalence of STIs: HIV, Hepatitis B, Hepatitis C, and Syphilis in a population deprived of freedom? To answer this question, this study was evaluated the prevalence of Hepatitis B, Hepatitis C, and Syphilis in a population deprived of freedom in a temporary correctional facility in the metropolitan region of Belo Horizonte, outlining a panorama in Brazil and in the world, furthermore this study evaluated the demographic and behavioral data of this population. To reach this objective, a quantitative and structures cross-sectional study was carried out using a social e behavioral survey, applied to 126 detainees. Rapit tests (RT) were performed for HIV, Hepatitis B, Hepatitis C, and Syphilis, the test results were subjected to univariate analysis (Chi-square test, Fisher’s exact test, and Student’s t-test) to identify sociodemographic and behavioral risk factors that could be used to conduct to multivariate analysis (logistic regression). This study was performed between March 2018 and September 2019. For the diagnosis of HIV two RTs were used (TR1 e TR2), for HBV, RT (RT-HBsAg), for Hepatitis C (RT-HCV), and Syphilis use of treponemal RT. The main results reported were the prevalence of HIV, 5.5%, HBV, 3.1%, HCV, 0.2%, and Syphilis 21.2%. The prevalence of HIV and Syphilis was higher than the general population and also, higher than most other correctional facilities, both in Brazil and in the other countries. The results of the univariate analysis found an association between the previous STI variable and a new STI diagnosis, we also found an association between the age of the participants and the prevalence of STI. A person with a previous STI had 3.71 times more chance for positivity in RT for any STI. When compared to detainees aged between 18 and 25, an individual aged 36 to 45 years is 3.89 times more likely to have a positive test for STI; those over 45 years of age are 9.97 times more likely to be positive for any of the diseases under study. In multivariate analysis with logistic regression, the proposed model was not able to predict whether the patient had any of the STIs, but it was a predictor for cases without an STI diagnosis. This data suggests that prevention and early treatment for HIV, HCV, HBV, and Syphilis for population deprived of freedom, are fundamental to breaking the chain of transmission, both inside and outside correctional facilities. In conclusion, this study allows us to affirm that the prevalence of STI is greater in deprived of freedom when compared to the general population. High age is a risk factor for STIs since people accumulate years of exposure without access to prevention supplies and early testing. In this study, we found a high risk for STI co-infection, especially among people who have already had a previous diagnosis. The high prevalence of STIs in correctional facilities is a public health problem that is also related to the suppression of human rights and the low quality of health care found in the prison structure.